INTERCULTURAL COMMUNICATION AND LANGUAGE LEARNING SOCIAL NETWORKS - Tatiana M. Gulaya; Svetlana A. Romanova (Статистика и экономика, 2016)
The paper outlines the importance of intercultural communication in the altered circumstances of today’s globalized world. Improving abilities in intercultural communication goes hand in hand with developing language learners’ communicative competence and cultural awareness. A basic understanding of cultural diversity can be obtained through the use of authentic language materials unlimited access to which is given by Web 2.0 tools. The paper highlights the use of language learning social networks which provide language learners with the opportunity to interact with native speakers of their target language and gain practical, real-life language skills.